1992
DOI: 10.1007/bf01270630
|View full text |Cite
|
Sign up to set email alerts
|

ALVIN investigation of an active propagating rift system, Galapagos 95.5� W

Abstract: Abstract. ALVIN investigations have defined the fine-scale structural and volcanic patterns produced by active rift and spreading center propagation and failure near 95.5°W on the Galapagos spreading center. Behind the initial lithospheric rifting, which is propagating nearly due west at about 50 km m.y.-1, a triangular block of preexisting lithosphere is being stretched and fractured, with some recent volcanism along curving fissures. A well-organized seaf.oor spreading center, an extensively faulted and fiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…If the inward facing scarps are the pseudofaults, they would in some ways be similar to the structures at the Galapagos 95.5°W propagator, where there is a topographically low area at the propagating rift tip bounded by inward facing pseudofault scarps. This tip depression eventually evolves to a V‐shaped trough, bounded on the other side by the gradually developing constructional axial ridge [ Hey et al , 1986, 1992; Kleinrock and Hey , 1989]. In this case the troughs bounding the A′ propagator could be tip depression wakes.…”
Section: Propagating Rift Interpretationmentioning
confidence: 99%
See 3 more Smart Citations
“…If the inward facing scarps are the pseudofaults, they would in some ways be similar to the structures at the Galapagos 95.5°W propagator, where there is a topographically low area at the propagating rift tip bounded by inward facing pseudofault scarps. This tip depression eventually evolves to a V‐shaped trough, bounded on the other side by the gradually developing constructional axial ridge [ Hey et al , 1986, 1992; Kleinrock and Hey , 1989]. In this case the troughs bounding the A′ propagator could be tip depression wakes.…”
Section: Propagating Rift Interpretationmentioning
confidence: 99%
“…If the outer boundary of this E scarp trough is the pseudofault, this would require an ∼2–3 Ma time lag between initial rifting and the formation of the E scarp at the constructional axis. In the Galapagos area, the time lag is ∼200,000 years, and the resulting constructional ridge forms much more gradually than the abrupt A and E scarps [ Hey et al , 1986, 1989, 1992; Kleinrock and Hey , 1989].…”
Section: Propagating Rift Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“… Christie and Sinton [1981] and Sinton et al [1983, 1991] showed that most propagating rifts are associated with along‐axis gradients to deeper bathymetry and increased extent of shallow level fractionation at the propagating tip; these gradients can extend for a few tens to a few hundreds of kilometers behind the rift tip. In contrast, along failing rifts the extent of shallow level fractionation typically decreases toward the rift tip, while the rift axis also increases in depth [ Sinton et al , 1983, 1991; Yonover et al , 1989; Hey et al , 1992]. However, near 93.25°W, MgO increases toward the tip of each limb and within the overlap zone, and the overlapping ridge axes become shallower than those outside the overlap zone on either side.…”
Section: Discussionmentioning
confidence: 99%